Fundus fluorescein angiographic assessment of patients with proliferative diabetic retinopathy and macular edema before and after intravitreal injection of Bevacizumab - ., Ankur; Kumar, Yogesh; Arora, Deepesh; Tyagi, Rupali; Mittal, Sanjeev Kumar (International Journal of Research in Medical Sciences, 2019)
Background: To assess the role of intravitreal bevacizumab (1.25 mg) in patients with proliferative diabetic retinopathy with macular edema in terms of change in leakage area and best-corrected visual acuity. Methods: This prospective randomized interventional study was conducted in the Department of Ophthalmology from September 2013 to August 2015 and included thirty eyes of twenty patients. After a detailed history and ocular examination, diagnosed cases of proliferative diabetic retinopathy (PDR) and diabetic macular edema (DME) underwent sequential fundus fluorescein angiography. Bevacizumab was administered intravitreally. Patients were assessed two hours after injection for anterior chamber reaction and intraocular pressure and were advised follow-ups at 24 hours and then at 1, 4, 8 and 12 weeks. For the outcome, the change of retinal new vessels by assessment of leakage area using Quantitative Planimetric Analysis (QPA) of photographs as well as the change in best-corrected visual acuity (BCVA) from baseline to the 12 weeks follow-up, were done. Results were analyzed statistically by applying t-test. Results: Intravitreal bevacizumab injection lead to a significant decrease in leakage in DME and PDR, and improvement in mean BCVA. The effect was maximum at 4 weeks which weaned off as the study progressed through it remains statistically significant at the end of 12 weeks. Conclusions: Intravitreal bevacizumab plays a major role in treating and reducing visual deterioration in patients with proliferative diabetic retinopathy and diabetic macular edema.